(untitled) (Al-Qamar, 2022)
Arabic is a symbol of religious identity and the liturgical language of the Kashmir. Arabic has always been an important part of the education of Kashmir. This article reflects the development and evolution of Arabic language in Kashmir. The Arabic influenced and produced impact on Kashmiri Language. As majority of Kashmiri People were Muslims from centuries, therefore their interest and attention towards the Arabic language was natural. Kashmiri poets are well known for their unique style and methodology. They made use of poetry skill in all prominent languages of the world. Few prominent Kashmiri saint/Intellectuals made use of Arabic as language of poetry. The Article also provides brief introduction of Scholars/Poets who made Arabic as language of their expressions.